2012
DOI: 10.1016/j.ijheatfluidflow.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irregular two-dimensional and three-dimensional surface roughness in turbulent channel flows

Abstract: a b s t r a c tWall-resolved Large Eddy Simulation of fully developed turbulent channel flows over two different rough surfaces is performed to investigate on the effects of irregular 2D and 3D roughness on the turbulence. The two geometries are obtained through the superimposition of sinusoidal functions having random amplitudes and different wave lengths. In the 2D configuration the irregular shape in the longitudinal direction is replicated in the transverse one, while in the 3D case the sinusoidal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 58 publications
4
13
0
Order By: Relevance
“…In fully rough regime, even though 2D and 3D rough walls are characterised by the same value r þ (% 20), the roughness function obtained with the 3D roughness is significantly higher than that obtained in the 2D case (DU þ ¼ 9:1 for 3D case and DU þ ¼ 7:6 for 2D one). This result was already pointed out by De Marchis and Napoli (2012), who concluded that the effects of 3D roughness on the mean velocities are higher than those of 2D roughness. Conversely, in transitional rough regime the velocity profiles achieved over 2D and 3D rough walls collapse each other, thus reaching the same value of roughness function DU þ ¼ 4:0.…”
Section: Mean Velocitysupporting
confidence: 73%
See 1 more Smart Citation
“…In fully rough regime, even though 2D and 3D rough walls are characterised by the same value r þ (% 20), the roughness function obtained with the 3D roughness is significantly higher than that obtained in the 2D case (DU þ ¼ 9:1 for 3D case and DU þ ¼ 7:6 for 2D one). This result was already pointed out by De Marchis and Napoli (2012), who concluded that the effects of 3D roughness on the mean velocities are higher than those of 2D roughness. Conversely, in transitional rough regime the velocity profiles achieved over 2D and 3D rough walls collapse each other, thus reaching the same value of roughness function DU þ ¼ 4:0.…”
Section: Mean Velocitysupporting
confidence: 73%
“…3(b). The profiles, as pointed out by De Marchis and Napoli (2012), show that the effects of both 2D and 3D wall roughness are mainly confined in the inner layer, whereas in the most of the outer layer all profiles are quite similar.…”
Section: Mean Velocitysupporting
confidence: 56%
“…As for the irregularly structured surface, the surface roughness was characterized by three-dimensinal irregular geometry [12]. To understand the influence of surface 3D morphology on the wetting behavior, the volume ratio χ was introduced to characterize the topography of irregularly micro-structured surface (Fig.…”
Section: Fig 5 Shows a Schematic Illustration Of Roughness In Distanmentioning
confidence: 99%
“…Although our previous study has investigated the characterization of the regularly micro-grooved surface relating to its anisotropic wetting properties [11], its fabrication was costly and time-consuming. Because of the easy fabrication of irregular structures, the irregularly micro-structured surfaces with wetting properties allow for new opportunities in controlling the microflows of fluid in micro-devices [12].…”
Section: Introductionmentioning
confidence: 99%
“…(2008),Flack (2009) andNapoli (2012) are included in the plot. The results are presented for 0 ES 0.38 at the highest Reynolds number and are found to show a trend similar to other observations.…”
mentioning
confidence: 99%